O corte do FBST em modelos de alta dimensionalidade - Poloniato Ferreira, Joao Carlos (Universidade Federal de São Carlos, 2018)
The problem of controlling the significance level of the FBST (Full Bayesian Significant Test) test is studied in the context of Bayesian models for density, thus, a Bayesian method is shown that works with density estimation estimation and how the FBST should be conducted in that situation with this method when it is desired to test if one population has certain density distribution or equality test of two populations. For this, a modified e-value definition is presented that is an alternative to calculate the FBST measure. At end a simulation study with different density distributions and analysis the power function of the test in cases of one and two populations.
The FBST cutoff in high dimensional models
Keywords: Testes bayesianos; Hipóteses precisas; Função poder; Bayesian test; Precise hypothesis; Power function; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA::ESTATISTICA::FUNDAMENTOS DA ESTATISTICA; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA::ESTATISTICA